UJICOBA PENANAMAN LADA - LADA (Micromelum minutum) UNTUK PEMBINAAN HABITAT KUPU – KUPU DI TAMAN NASIONAL BANTIMURUNG BULUSARAUNG - Heri Suryanto (Fakultas Kehutanan Universitas Mulawarman, 2019)
Butterfly is a typical fauna in Bantimurung Bulusaraung National Park. Its population are more and more decreased in nature due to decreased of feed plant of butterfly caused by logging and encroachment. In order to get effective and efficient method, research was conducted. Butterfly improvement research in Bantimurung Bulusaraung National Park was carried out in the evaluation of plant growth. Planting trials were carried out in using the Randomysed Completely Block Design (RCBD) method with 4 levels of fertilization treatment, i.e control, 300gr fertilizer dosage for planting holes, 600 gr for planting holes and 900 g for planting holes. The results showed that the best dose of manure in Micromelum minutum 600 gr treatment gave the best value of number of leaves. Chlorosis made growth of the plants were not optimal due to fast drainase of the soil.